An Analysis of the Factors Associated with the Seasonal Variability of Physical Activity in Natural Environments in a Sample of Lithuanian Adults - Rasa Jankauskiene; Migle Baceviciene (Behavioral Sciences)
Engagement in physical activity (PA) in natural environments is known to promote physical and psychological well-being, yet little is known about how such activity fluctuates across seasons and how it relates to individual characteristics and quality of life (QoL). This study aimed to assess the seasonal variability of PA in nature and examine its associations with sociodemographic factors, nature-related experiences, and overall QoL in a sample of Lithuanian adults. A total of 924 participants (680 women and 244 men) with a mean age of 40.0 ± 12.4 years completed an online survey. The study measures included sociodemographic characteristics, nature proximity, exposure, connectedness, perceived restoration in nature and QoL measured by the WHOQOL. Based on self-reported seasonal behaviour, participants were categorized into three groups: irregular or no PA in natural environments, seasonal variability, and regular year-round PA in natural environments. In the present study, we observed the lowest rates of PA in natural environments in winter and the highest in summer. Comparative analyses revealed that individuals with regular PA in natural environments reported significantly greater financial security, nature exposure and connectedness, proximity to green spaces, and overall QoL compared to less regular PA in nature groups. A multiple regression analysis identified financial security, nature proximity, nature exposure, connectedness, and perceived restoration in nature as significant and positive predictors of QoL. These findings point to the problem of inequity and suggest that inequitable access to PA in natural environments manifests as a higher seasonality of PA in nature. The practical implications of the study highlight the importance of addressing equity and promoting consistent PA in nature throughout seasons. During the dark, wet, and cold periods, it is important to implement targeted interventions that improve access to natural environments for individuals with lower financial security. This could help reduce inequity in physical activity. Promoting access to green spaces and fostering nature connectedness may be particularly valuable strategies in public health interventions aimed at enhancing QoL across diverse populations.